Preparation method and application of monolithic ruthenium-based ammonia decomposition catalyst

Through the design of the monolithic Ru-based catalyst and the preparation method of the original cell replacement method, the problems of low-temperature activity and insufficient mass transfer/heat transfer performance of the existing ammonia decomposition catalysts are solved, and efficient, stable and easy-to-operate ammonia decomposition hydrogen production is achieved. catalyst.

CN116099547BActive Publication Date: 2025-01-21FZU ZIJIN HYDROGEN POWER TECH CO LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310131528.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-17
Publication Date
2025-01-21
Estimated Expiration
2043-02-17

AI Technical Summary

Technical Problem

The existing ammonia decomposition catalysts have problems such as low low temperature catalytic activity, poor mass/heat transfer performance, insufficient mechanical stability, complex preparation process and easy to lead to low sintering and utilization of active components.

Method used

A monolithic Ru-based catalyst is used, and the catalyst is prepared through a metal skeleton carrier and loaded ruthenium or additive-modified ruthenium, and the original cell replacement method is used to ensure that the Ru active component is uniformly and firmly anchored on the surface of the metal carrier.

Benefits of technology

It achieves high low-temperature ammonia decomposition activity, good mass/heat transfer performance, strong structural stability, simple preparation, easy disassembly and loading, avoids turbulence problems caused by methanation of carrier carbon and uneven fluid distribution, and improves the performance of the catalyst. Overall performance.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention discloses an integral ruthenium-based catalyst and its preparation method and application. The catalyst comprises an active component ruthenium, a skeleton metal carrier and an auxiliary agent; the active metal ruthenium is firmly and evenly anchored on the surface of the metal carrier by a primary cell replacement method, and the auxiliary agent is introduced for modification. The catalyst has good mass transfer / heat transfer performance, strong structural stability, no need for secondary molding, and is easy to disassemble and load, achieving a good low-temperature ammonia decomposition effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalytic ammonia decomposition, and specifically relates to an integral ruthenium-based catalyst and a preparation method and application thereof. Background Art

[0002] Due to the increasing depletion of oil resources and the environmental pressure caused by burning fossil energy, people are forced to actively seek new alternative energy sources. Among them, clean, efficient and widely available hydrogen energy has attracted much attention. Hydrogen energy has a high calorific value (1.4×10 5 kJ kg -1 ), which can not only provide heat energy through combustion, but also provide electrical energy through fuel cells. However, hydrogen has a wide explosion limit and harsh liquefaction conditions, which makes its storage and transportation difficult and has poor safety. Ammonia, as an excellent hydrogen storage carrier (hydrogen content 17.3wt%), has the advantages of easy liquefaction, easy storage and easy transportation. Therefore, using ammonia as a hydrogen storage medium, producing hydrogen on-site through ammonia decomposition reaction, and developing a distinctive "ammonia-hydrogen" technology route are important paths to promote the development of the hydrogen energy industry. Among them, the development of efficient ammonia decomposition catalysts for hydrogen production is the key.

[0003] At present, the ammonia decomposition catalyst system mainly includes precious metal catalysts (Ru) and transition metal catalysts (Fe and Ni). Experimental and theoretical calculation results show that Ru is the metal with the highest ammonia decomposition activity, and generally at around 500°C, ammonia can be completely converted. Ni and Fe transition metal ammonia decomposition temperatures are as high as 750°C, but their reserves are abundant and the price is low.

[0004] A Chinese patent (CN108212166A) discloses a Ni-based ammonia decomposition catalyst that is easy to disassemble. They first prepare Ni-based catalyst powder, then mix the active powder with a pore-forming agent and a binder, and then prepare the catalyst after roasting and molding. The catalyst preparation process is complicated, and after pressure molding, the mass transfer capacity is poor, resulting in low utilization of active components; during long-term operation, the active components are easy to sinter, affecting the catalytic efficiency; in addition, due to poor heat transfer effect, the bed temperature distribution is uneven, which also leads to low utilization of the catalyst active components.

[0005] Monolithic catalysts have been widely verified to significantly optimize the mass transfer / heat transfer performance of catalysts. A Chinese patent (CN101147863A) discloses an integral nickel-based ammonia decomposition catalyst. They place metal fibers, alumina carriers and cellulose in water for pulping and mixing, and then prepare a carrier through calcination and reduction treatment, and then impregnate the prepared carrier with active components. The monolithic catalyst can achieve an ammonia conversion rate of 99% at 600°C. However, the preparation process of this type of catalyst is complicated, and under long-term reaction, due to the inconsistent expansion coefficients of oxides and metals, the active components will fall off, affecting the stability of the catalyst; in addition, the detached catalyst powder will cause the reactor to be blocked, increase pipeline resistance, and damage the valve. Summary of the invention

[0006] Therefore, the technical problem to be solved by the present invention is to overcome the defects of low low-temperature catalytic activity and poor mass transfer / heat transfer performance of the ammonia decomposition catalyst in the prior art, thereby providing an integral Ru-based catalyst with high low-temperature ammonia decomposition activity, good mass transfer / heat transfer performance, strong mechanical stability, simple preparation, and easy disassembly and loading, and applying it to the ammonia decomposition reaction.

[0007] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention is as follows:

[0008] An integral Ru-based ammonia decomposition catalyst comprises a metal skeleton carrier and ruthenium or promoter-modified ruthenium loaded thereon, wherein the mass percentage of ruthenium in the catalyst is 0.1-5.0%, the mass percentage of the promoter in the catalyst is 0.1-2.0%, and the balance is the metal skeleton carrier.

[0009] As a preferred embodiment, the auxiliary agent is selected from at least one of alkali metals, alkaline earth metals, lanthanide rare earth metals, zinc, manganese, tungsten, vanadium, molybdenum, iron and nickel.

[0010] As a preferred embodiment, the material of the metal skeleton carrier is any one of nickel, iron, aluminum, nickel silver, brass, and copper.

[0011] As a preferred embodiment, the morphological structure of the metal skeleton carrier is selected from any one of wire, wire mesh, foil, foam, fiber, fiber felt, tube, and particle. The diameter of the wire is 0.1-10.00 mm; the wire mesh is a net woven from the wire, with a mesh count of 10-1000; the thickness of the foil is 0.1-10 mm; the open pore size of the foam is 10-200 PPI; the fiber is a fiber with a diameter of 1-100 microns; the fiber felt is a fiber felt with a three-dimensional porous structure sintered from the fiber with a diameter of 100 microns; the outer diameter of the tube is 1-25 mm, and the wall thickness is 0.1-5 mm; the particle size of the particle is 10-200 microns.

[0012] As a preferred solution, the porosity of the monolithic Ru-based catalyst is 30 to 90%.

[0013] A method for preparing the monolithic Ru-based catalyst described in the present invention comprises the following steps:

[0014] S1: clean the metal skeleton carrier with acetone and dry it for later use;

[0015] S2 prepares an aqueous solution containing a certain concentration of a ruthenium compound and an auxiliary agent;

[0016] S3 places the cleaned metal skeleton carrier into the solution prepared in S2, and the two undergo a primary cell replacement reaction. The obtained catalyst precursor is dried at 50-120°C for 0.5-12 hours, then calcined at 300-800°C for 0.5-12 hours, and then reduced at 300-800°C in a hydrogen atmosphere for 0.5-48 hours to obtain the integral Ru-based catalyst.

[0017] As a preferred embodiment, the ruthenium compound is ruthenium nitrate, ruthenium chloride, ruthenium acetate, chlororuthenic acid or chlororuthenate. Further, the chlororuthenate is ammonium chlororuthenate, sodium chlororuthenate or potassium chlororuthenate.

[0018] As a preferred embodiment, the auxiliary metal compound is selected from at least one of nitrates, sulfates, hydrochlorides, oxalates, acetates, and acetylacetonates.

[0019] Compared with the prior art, the present invention has the following significant beneficial effects:

[0020] The integral Ru-based catalyst provided by the present invention has the advantages of high low-temperature ammonia decomposition activity, good mass transfer / heat transfer performance, strong structural stability, simple preparation, and easy disassembly and loading. Compared with the Ru-based catalyst prepared by the prior art, the catalyst can avoid the methanation of the carrier carbon during the reaction, while enhancing the thermal conductivity of the catalyst to make the bed temperature uniformly distributed; in addition, the integral catalyst has an open network structure, which can avoid mass transfer problems such as turbulence, channeling and short circuiting caused by uneven fluid distribution, and solve the problem of limited mass transfer / heat transfer of existing catalysts in industrial applications. Secondly, by adopting the primary cell replacement method to prepare the Ru-based catalyst, the Ru active component can be evenly and firmly anchored on the surface of the metal carrier, greatly improving the catalytic performance. Therefore, the integral Ru-based catalyst of the present invention is an excellent ammonia decomposition hydrogen production catalyst, which has a reaction temperature of 550°C and an air velocity of 8000mL g -1 h -1 Under the condition of , the catalyst of the present invention can achieve an ammonia conversion rate of 99.7%. The catalyst of the present invention has a simple preparation process, readily available raw materials, low cost, strong process controllability, and is suitable for mass production and industrial application. DETAILED DESCRIPTION

[0021] The technical solution of the present invention is further described in detail and completely below in conjunction with embodiments and comparative examples.

[0022] Example 1

[0023] ① At room temperature, place 1 gram of Fe-foam with a porosity of 100 PPI (pores per inch) in an acetone solution for ultrasonic treatment for 1 hour, then wash and dry;

[0024] ② Weigh 0.21 g of ruthenium nitrate aqueous solution containing 0.12 g / g of ruthenium and dilute it to 0.8 g with water. Then weigh 0.013 g of potassium nitrate and add it to the prepared ruthenium nitrate solution. Transfer the prepared solution into a 5 ml beaker.

[0025] ③ At room temperature, immerse the washed foam iron carrier in the solution prepared in ②, so that the iron on the surface of the foam iron and the ruthenium ions in the ruthenium nitrate solution undergo a primary battery replacement reaction. After reacting for 1 hour, place the sample in an oven at 80°C for 12 hours. Then, calcine the obtained sample at 450°C in air for 2 hours, and then reduce it at 500°C for 3 hours in a hydrogen-nitrogen mixed gas atmosphere (hydrogen gas volume fraction 5%) to obtain the monolithic Ru-based catalyst;

[0026] ④At different temperatures, the flow rate was 40 mL min -1 The activity of the catalyst was evaluated by pure ammonia gas, with a catalyst loading of 0.3 g and a space velocity of 8000 mL g -1 h -1 According to the formula: ammonia conversion rate = (initial ammonia content - tail gas ammonia content) / initial ammonia content × 100%, the specific results are shown in Table 1.

[0027] The catalyst prepared in step ③ was measured by inductively coupled plasma atomic emission spectroscopy (ICP), and it was found that the mass content of K in the catalyst prepared in this example was 0.96%, and the mass content of the active component Ru was 2.5%.

[0028] In step ① of this embodiment, the PPI of the foamed iron can be 10-200, and the other conditions remain unchanged.

[0029] In step ② of this embodiment, the ruthenium nitrate aqueous solution containing 0.12 g / g of ruthenium can be 0.01 to 8 g, and the other conditions remain unchanged.

[0030] In step ② of this embodiment, potassium nitrate can be 0.001 to 1.3 g, and the other conditions remain unchanged.

[0031] In step ③ of this embodiment, the original battery replacement reaction time can be 0.1 to 12 hours, and the other conditions remain unchanged.

[0032] In step ③ of this embodiment, the drying temperature can be 50-120° C., and the other conditions remain unchanged.

[0033] In step ③ of this embodiment, the calcination temperature may be 300-800° C., and the other conditions remain unchanged.

[0034] In step ③ of this embodiment, the calcination time can be 0.5 to 12 hours, and the other conditions remain unchanged.

[0035] In step ③ of this embodiment, the reduction temperature can be 300-700° C., and the other conditions remain unchanged.

[0036] In step ③ of this embodiment, the reduction time can be 0.5 to 24 hours, and the other conditions remain unchanged.

[0037] Example 2

[0038] ① At room temperature, place 1 gram of iron fiber (30 microns in diameter and 5 mm in length, denoted as Fe-fiber) in an acetone solution for 1 hour, wash and dry;

[0039] ② Weigh 0.084 g of ruthenium nitrate aqueous solution containing 0.12 g / g of ruthenium and dilute it to 1 g with water. Then weigh 0.013 g of potassium nitrate and add it to the prepared ruthenium nitrate solution. Transfer the prepared solution into a 5 ml beaker.

[0040] ③ At room temperature, immersing the washed iron fiber carrier in the solution prepared in ②, and preparing the monolithic Ru-based catalyst in the same manner as step ③ in Example 1;

[0041] ④ The catalyst evaluation conditions were the same as in Example 1. The specific results are shown in Table 1.

[0042] The catalyst prepared in step ③ was measured by ICP, and it was found that in the catalyst prepared in this example, the mass content of K was 1.0%, and the mass content of the active component Ru was 1.0%.

[0043] In step ① of this embodiment, the diameter of the iron fiber can be 1 to 100 microns, and the length can be 1 to 10 millimeters, and the other conditions remain unchanged.

[0044] In step ② of this embodiment, the ruthenium nitrate aqueous solution containing 0.12 g / g of ruthenium can be 0.01 to 8 g, and the other conditions remain unchanged.

[0045] In step ② of this embodiment, potassium nitrate can be 0.001 to 1.3 g, and the other conditions remain unchanged.

[0046] In step ③ of this embodiment, the original battery replacement reaction time can be 0.1 to 12 hours, and the other conditions remain unchanged.

[0047] In step ③ of this embodiment, the drying temperature can be 50-120° C., and the other conditions remain unchanged.

[0048] In step ③ of this embodiment, the calcination temperature may be 300-800° C., and the other conditions remain unchanged.

[0049] In step ③ of this embodiment, the calcination time can be 0.5 to 12 hours, and the other conditions remain unchanged.

[0050] In step ③ of this embodiment, the reduction temperature can be 300-700° C., and the other conditions remain unchanged.

[0051] In step ③ of this embodiment, the reduction time can be 0.5 to 24 hours, and the other conditions remain unchanged.

[0052] Example 3

[0053] ① At room temperature, 1 gram of iron particles (particle size 500 microns, denoted as Fe-granule) were placed in an acetone solution for 1 hour of ultrasonic treatment, then washed and dried;

[0054] ② Weigh 0.21 g of an aqueous solution of ruthenium nitrate containing 0.12 g / g of ruthenium and dilute it to 1 g with water. Then weigh 0.026 g of potassium nitrate and add it to the prepared ruthenium nitrate solution. Transfer the prepared solution into a 5 ml beaker.

[0055] ③ At room temperature, immersing the washed iron particle carrier in the solution prepared in ②, and preparing the monolithic Ru-based catalyst in the same manner as step ③ in Example 1;

[0056] ④ The catalyst evaluation conditions were the same as those in Example 1. The specific results are shown in Table 1.

[0057] The catalyst prepared in step ③ was measured by ICP, and it was found that the mass content of K in the catalyst prepared in this example was 1.9%, and the mass content of the active component Ru was 2.5%.

[0058] In step ① of this embodiment, the size of the iron particles can be 100 to 1000 microns, and the other conditions remain unchanged.

[0059] In step ② of this embodiment, the ruthenium nitrate aqueous solution containing 0.12 g / g of ruthenium can be 0.01 to 8 g, and the other conditions remain unchanged.

[0060] In step ② of this embodiment, potassium nitrate can be 0.001 to 1.3 g, and the other conditions remain unchanged.

[0061] In step ③ of this embodiment, the original battery replacement reaction time can be 0.1 to 12 hours, and the other conditions remain unchanged.

[0062] In step ③ of this embodiment, the drying temperature can be 50-120° C., and the other conditions remain unchanged.

[0063] In step ③ of this embodiment, the calcination temperature may be 300-800° C., and the other conditions remain unchanged.

[0064] In step ③ of this embodiment, the calcination time can be 0.5 to 12 hours, and the other conditions remain unchanged.

[0065] In step ③ of this embodiment, the reduction temperature can be 300-700° C., and the other conditions remain unchanged.

[0066] In step ③ of this embodiment, the reduction time can be 0.5 to 24 hours, and the other conditions remain unchanged.

[0067] Example 4

[0068] ① At room temperature, place 1 g of foamed iron (porosity 100 PPI) in an acetone solution for 1 hour, wash and dry;

[0069] ② Weigh 0.013 g of potassium nitrate and dissolve it in 0.8 g of distilled water. Transfer the solution into a 5 ml beaker.

[0070] ③ At room temperature, the washed foamed iron carrier is immersed in the solution prepared in ②, and placed in an oven at 80° C. for drying for 12 hours. The obtained sample is then calcined at 450° C. for 2 hours in air, and then reduced at 500° C. for 3 hours in a hydrogen-nitrogen mixed gas atmosphere (hydrogen gas volume fraction 5%) to obtain a monolithic catalyst;

[0071] ④ The catalyst evaluation conditions were the same as in Example 1. The specific results are shown in Table 1.

[0072] The catalyst prepared in step ③ was measured by ICP, and it was found that the mass content of K in the catalyst prepared in this example was 1.0%.

[0073] In step ① of this embodiment, the PPI of the foamed iron can be 10-200, and the other conditions remain unchanged.

[0074] In step ② of this embodiment, potassium nitrate can be 0.001 to 1.3 g, and the other conditions remain unchanged.

[0075] Example 5

[0076] ① At room temperature, 1 g of nickel foam (porosity 70 PPI, denoted as Ni-foam) was placed in an acetone solution for 1 hour, ultrasonicated, washed and dried;

[0077] ② Weigh 0.21 g of ruthenium nitrate aqueous solution containing 0.12 g / g of ruthenium and dilute it to 0.8 g with water. Then weigh 0.013 g of potassium nitrate and add it to the prepared ruthenium nitrate solution. Transfer the prepared solution into a 5 ml beaker.

[0078] ③ At room temperature, immerse the washed nickel foam carrier in the solution prepared in ② to cause a primary battery replacement reaction between the nickel on the surface of the nickel foam and the ruthenium ions in the ruthenium nitrate solution. After reacting for 4 hours, place the carrier in an oven at 100° C. for 12 hours, then calcine the obtained sample in air at 450° C. for 2 hours, and then reduce it at 500° C. for 3 hours in a hydrogen-nitrogen mixed gas atmosphere (hydrogen gas volume fraction 5%) to obtain the monolithic Ru-based catalyst;

[0079] ④ The catalyst evaluation conditions were the same as in Example 1. The specific results are shown in Table 1.

[0080] The catalyst prepared in step ③ was measured by ICP, and it was found that in the catalyst prepared in this example, the mass content of K was 0.98%, and the mass content of the active component Ru was 2.5%.

[0081] In step ① of this embodiment, the PPI of the foamed iron can be 10-150, and the other conditions remain unchanged.

[0082] In step ② of this embodiment, the ruthenium nitrate aqueous solution containing 0.12 g / g of ruthenium can be 0.01 to 8 g, and the other conditions remain unchanged.

[0083] In step ② of this embodiment, potassium nitrate can be 0.001 to 1.3 g, and the other conditions remain unchanged.

[0084] In step ③ of this embodiment, the original battery replacement reaction time can be 1 to 24 hours, and the other conditions remain unchanged.

[0085] In step ③ of this embodiment, the drying temperature can be 50-120° C., and the other conditions remain unchanged.

[0086] In step ③ of this embodiment, the calcination temperature may be 300-900° C., and the other conditions remain unchanged.

[0087] In step ③ of this embodiment, the calcination time can be 0.5 to 12 hours, and the other conditions remain unchanged.

[0088] In step ③ of this embodiment, the reduction temperature can be 300-800° C., and the other conditions remain unchanged.

[0089] In step ③ of this embodiment, the reduction time can be 0.5 to 48 hours, and the other conditions remain unchanged.

[0090] Example 6

[0091] ① At room temperature, 1 g of nickel fiber (30 μm in diameter and 5 mm in length, denoted as Ni-fiber) was placed in an acetone solution for 1 hour for ultrasonic treatment, then washed and dried;

[0092] ② Weigh 0.084 g of ruthenium nitrate aqueous solution containing 0.12 g / g of ruthenium and dilute it to 0.8 g with water. Then weigh 0.013 g of potassium nitrate and add it to the prepared ruthenium nitrate solution. Transfer the prepared solution into a 5 ml beaker.

[0093] ③ At room temperature, immersing the washed nickel fiber support in the solution prepared in ②, and preparing the monolithic Ru-based catalyst in the same manner as step ③ in Example 5;

[0094] ④ The catalyst evaluation conditions were the same as those in Example 1. The specific results are shown in Table 1.

[0095] The catalyst prepared in step ③ was measured by ICP, and it was found that the mass content of K in the catalyst prepared in this example was 0.9%, and the mass content of the active component Ru was 1.1%.

[0096] In step ① of this embodiment, the diameter of the nickel fiber is 1 to 100 microns, and the length can be 1 to 10 millimeters, and the other conditions remain unchanged.

[0097] In step ② of this embodiment, the ruthenium nitrate aqueous solution containing 0.12 g / g of ruthenium can be 0.01 to 8 g, and the other conditions remain unchanged.

[0098] In step ② of this embodiment, potassium nitrate can be 0.001 to 1.3 g, and the other conditions remain unchanged.

[0099] In step ③ of this embodiment, the original battery replacement reaction time can be 1 to 24 hours, and the other conditions remain unchanged.

[0100] In step ③ of this embodiment, the drying temperature can be 50-120° C., and the other conditions remain unchanged.

[0101] In step ③ of this embodiment, the calcination temperature may be 300-900° C., and the other conditions remain unchanged.

[0102] In step ③ of this embodiment, the calcination time can be 0.5 to 12 hours, and the other conditions remain unchanged.

[0103] In step ③ of this embodiment, the reduction temperature can be 300-800° C., and the other conditions remain unchanged.

[0104] In step ③ of this embodiment, the reduction time can be 0.5 to 48 hours, and the other conditions remain unchanged.

[0105] Example 7

[0106] ① At room temperature, place 1 gram of nickel foil (thickness 0.1-10 mm, denoted as Ni-foil) in an acetone solution for 1 hour, wash and dry;

[0107] ② Weigh 0.084 g of ruthenium nitrate aqueous solution containing 0.12 g / g of ruthenium and dilute it to 0.8 g with water. Then weigh 0.026 g of potassium nitrate and add it to the prepared ruthenium nitrate solution. Transfer the prepared solution into a 5 ml beaker.

[0108] ③ At room temperature, immersing the washed nickel foil carrier in the solution prepared in ②, and preparing the monolithic Ru-based catalyst in the same manner as step ③ in Example 5;

[0109] ④ The catalyst evaluation conditions were the same as in Example 1. The specific results are shown in Table 1.

[0110] The catalyst prepared in step ③ was measured by ICP, and it was found that the mass content of K in the catalyst prepared in this example was 2.0%, and the mass content of the active component Ru was 2.6%.

[0111] In step ① of this embodiment, the thickness of the nickel foil is 0.1 to 10 mm, and the other conditions remain unchanged.

[0112] In step ② of this embodiment, the ruthenium nitrate aqueous solution containing 0.12 g / g of ruthenium can be 0.01 to 8 g, and the other conditions remain unchanged.

[0113] In step ② of this embodiment, potassium nitrate can be 0.001 to 1.3 g, and the other conditions remain unchanged.

[0114] In step ③ of this embodiment, the original battery replacement reaction time can be 1 to 24 hours, and the other conditions remain unchanged.

[0115] In step ③ of this embodiment, the drying temperature can be 50-120° C., and the other conditions remain unchanged.

[0116] In step ③ of this embodiment, the calcination temperature may be 300-900° C., and the other conditions remain unchanged.

[0117] In step ③ of this embodiment, the calcination time can be 0.5 to 12 hours, and the other conditions remain unchanged.

[0118] In step ③ of this embodiment, the reduction temperature can be 300-800° C., and the other conditions remain unchanged.

[0119] In step ③ of this embodiment, the reduction time can be 0.5 to 48 hours, and the other conditions remain unchanged.

[0120] Example 8

[0121] ① At room temperature, place 1 gram of foamed copper (a copper-nickel alloy with a porosity of 50 PPI) in an acetone solution and ultrasonicate for 1 hour, then wash and dry;

[0122] ② Weigh 0.21 g of ruthenium nitrate aqueous solution containing 0.12 g / g of ruthenium and dilute it to 0.8 g with water. Then weigh 0.013 g of potassium nitrate and add it to the prepared ruthenium nitrate solution. Transfer the prepared solution into a 5 ml beaker.

[0123] ③ At room temperature, immerse the washed copper foam carrier in the solution prepared in ② to cause the nickel on the surface of the copper foam and the ruthenium ions in the copper and ruthenium nitrate solution to undergo a primary cell replacement reaction. After reacting for 2 hours, place the carrier in an oven at 100° C. for 12 hours, then calcine the obtained sample in air at 350° C. for 2 hours, and then reduce the sample at 500° C. for 3 hours in a hydrogen-nitrogen mixed gas atmosphere (hydrogen gas volume fraction 5%) to obtain the monolithic Ru-based catalyst;

[0124] ④ The catalyst evaluation conditions were the same as those in Example 1. The specific results are shown in Table 1.

[0125] The catalyst prepared in step ③ was measured by ICP, and it was found that in the catalyst prepared in this example, the mass content of K was 0.98%, and the mass content of the active component Ru was 2.5%.

[0126] In step ① of this embodiment, the PPI of the white copper foam can be 20-150, and the other conditions remain unchanged.

[0127] In step ② of this embodiment, the ruthenium nitrate aqueous solution containing 0.12 g / g of ruthenium can be 0.01 to 8 g, and the other conditions remain unchanged.

[0128] In step ② of this embodiment, potassium nitrate can be 0.001 to 1.3 g, and the other conditions remain unchanged.

[0129] In step ③ of this embodiment, the original battery replacement reaction time can be 0.1 to 10 hours, and the other conditions remain unchanged.

[0130] In step ③ of this embodiment, the drying temperature can be 50-100° C., and the other conditions remain unchanged.

[0131] In step ③ of this embodiment, the calcination temperature may be 300-500° C., and the other conditions remain unchanged.

[0132] In step ③ of this embodiment, the calcination time can be 0.5 to 6 hours, and the other conditions remain unchanged.

[0133] In step ③ of this embodiment, the reduction temperature can be 300-600° C., and the other conditions remain unchanged.

[0134] In step ③ of this embodiment, the reduction time can be 0.5 to 24 hours, and the other conditions remain unchanged.

[0135] Comparative Example 1

[0136] ① Weigh 0.108 g of an aqueous solution of ruthenium nitrate containing 0.12 g / g of ruthenium and dilute it to 1 g with water. Then weigh 0.013 g of potassium nitrate and add it to the prepared ruthenium nitrate solution. Transfer the solution to a 5 ml beaker.

[0137] ② Weigh 1 gram of commercial alumina nanoparticles and immerse an equal volume of them in the prepared solution at room temperature. Then place the obtained material in an oven at 80°C for 12 hours, then calcine it at 450°C in air for 2 hours, and then reduce it at 500°C for 3 hours in a hydrogen-nitrogen mixed gas atmosphere (hydrogen gas volume fraction 5%) to obtain a comparative catalyst;

[0138] ③At different temperatures, the flow rate was 40 mL min -1 The activity of the catalyst was evaluated by pure ammonia gas, with a catalyst loading of 0.3 g and a particle size of 250-600 μm at a space velocity of 8000 mL g -1 h -1 According to the formula: ammonia conversion rate = (initial ammonia content - tail gas ammonia content) / initial ammonia content × 100%, the specific results are shown in Table 1.

[0139] Comparative Example 2

[0140] The washed Fe-foam was prepared in the same manner as step ① in Example 1, and the carrier was evaluated. The evaluation conditions and calculation method were the same as in Example 1, and the specific results are shown in Table 1.

[0141] Comparative Example 3

[0142] The washed Ni-foam was prepared in the same manner as step ① in Example 4, and the carrier was evaluated. The evaluation conditions and calculation method were the same as in Example 1, and the specific results are shown in Table 1.

[0143] Comparative Example 4

[0144] The washed NiCu-foam was prepared in the same manner as step ① in Example 7, and the carrier was evaluated. The evaluation conditions and calculation method were the same as those in Example 1, and the specific results are shown in Table 1.

[0145] Table 1 Catalytic performance of catalysts of Examples 1-9 and Comparative Examples 1-4 in ammonia decomposition hydrogen production reaction at different reaction temperatures

[0146] 500℃ 550℃ 600℃ 650℃ Example 1 85.3 99.7 / / Example 2 77.7 92.5 99.4 / Example 3 81.1 98.9 99.5 / Example 4 59.1 84.6 99.2 99.8 Example 5 83.9 99.4 / / Example 6 75.6 93.7 99.4 / Example 7 84.5 97.9 99.5 / Example 8 80.3 95.6 99.3 / Comparative Example 1 65.6 89.2 98.5 99.4 Comparative Example 2 15.4 50.0 71.1 98.5 Comparative Example 3 9.5 26.2 47.8 71.6 Comparative Example 4 10.4 30.6 52.9 80.7

[0147] As shown in Table 1, the catalyst prepared by Example 1 of the present invention has the best reaction performance. -1 h -1Under the conditions of , the ammonia conversion rate can reach 99.7%. This shows that the Fe carrier is more suitable for the preparation method described in the patent. Through comparative examples, it was found that the reaction performance of the carriers was relatively low. After the original cell replacement and K modification, the ammonia decomposition activity of the catalyst was greatly improved. In addition, under the same K and Ru loading, the reaction performance of the integral catalyst is higher than that of the powder catalyst. This shows that the introduction of a three-dimensional metal carrier is conducive to improving the mass transfer and heat transfer of the catalyst, thereby improving the reaction performance of the catalyst.

[0148] It should be pointed out that the above are only some embodiments of the present invention and should not be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above contents of the present invention all fall within the scope of protection of the present invention.

Claims

1. An application of an integral ruthenium-based ammonia decomposition catalyst, characterized in that: The monolithic ruthenium-based ammonia decomposition catalyst comprises an active component of ruthenium, a skeleton metal carrier and an additive; the active component of ruthenium is firmly and evenly anchored on the surface of the metal carrier by a galvanic cell replacement method, and the galvanic cell replacement reaction time is 0.1 to 24 hours; and the additive is introduced to modify the active component; The metal carrier is any one of nickel, iron and cupronickel; The carrier is in the form of any one of foam, wire, net, fiber, fiber felt, foil, tube, and particle; The auxiliary agent is potassium nitrate; The monolithic ruthenium-based ammonia decomposition catalyst is used for decomposing ammonia to produce hydrogen.

2. The use of the monolithic ruthenium-based ammonia decomposition catalyst according to claim 1, characterized in that: The active component is ruthenium, which accounts for 0.1-5.0% of the catalyst in terms of mass percentage, the auxiliary agent accounts for 0.1-3.0% of the catalyst, and the remainder is the skeleton carrier.

3. The use of the monolithic ruthenium-based ammonia decomposition catalyst according to claim 1, characterized in that: The ruthenium source is any one of ruthenium nitrate, ruthenium chloride, ruthenium acetate, chlororuthenic acid or chlororuthenate.

4. The use of the monolithic ruthenium-based ammonia decomposition catalyst according to claim 3, characterized in that: The chlororuthenate is any one of ammonium chlororuthenate, sodium chlororuthenate or potassium chlororuthenate.

5. The use of the monolithic ruthenium-based ammonia decomposition catalyst according to claim 1, characterized in that: The preparation method of the monolithic ruthenium-based ammonia decomposition catalyst comprises the following steps: S1, placing the metal carrier in an acetone solution for ultrasonic cleaning; S2. preparing an aqueous solution containing an auxiliary agent and a ruthenium source at room temperature; S3, placing the metal carrier in the above solution at room temperature, and causing the carrier metal and ruthenium ions to undergo a primary cell replacement reaction to obtain a catalyst precursor; S4. The catalyst precursor is dried, calcined and reduced to obtain the monolithic ruthenium-based catalyst.

6. The use of the monolithic ruthenium-based ammonia decomposition catalyst according to claim 5, characterized in that: The drying temperature is 50-120° C., and the drying time is 0.5-12 hours.

7. The use of the monolithic ruthenium-based ammonia decomposition catalyst according to claim 5, characterized in that: The calcination temperature is 300 to 900° C., and the calcination time is 0.5 to 12 hours.

8. The use of the monolithic ruthenium-based ammonia decomposition catalyst according to claim 5, characterized in that: The reduction temperature is 300 to 800° C., and the reduction time is 0.5 to 48 hours.

Citation Information

Patent Citations

  • Integral ammonia decomposition hydrogen producing catalyst

    CN101147863A

  • Ammonia decomposition catalyst easy to disassemble and regenerate and preparation method thereof

    CN108212166A

  • Packaged catalyst, preparation method and application of packaged catalyst

    CN104069869A

  • Method for intensifying carbon dioxide catalytic hydrogenation reaction

    CN110368945A